2018
DOI: 10.14740/jh411w
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anemia in Type 2 Diabetic Patients

Abstract: Background: The aim of the study was to determine the prevalence of anemia in patients with type 2 diabetes and to assess the risk of anemia according to gender, age and glycemic control. Methods: The study group comprised of patients with type 2 diabetes attending Outpatient Diabetic Department of Amiri Hospital (Al-Asimah Capital area) from January 1, 2016 to December 31, 2017. Patients were divided into groups according to glycemic status and gender. Glycated hemoglobin (HbA1C) values and hemoglobin (Hb) le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
28
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 20 publications
(24 reference statements)
8
28
4
Order By: Relevance
“…Similar to our study, AlDallal et al [37] found that females with T2DM are at higher risk of anemia than males. This is consistent with findings of Alsayegh et al which reported a prevalence of 35.8% in females versus 21.3% in males [49].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to our study, AlDallal et al [37] found that females with T2DM are at higher risk of anemia than males. This is consistent with findings of Alsayegh et al which reported a prevalence of 35.8% in females versus 21.3% in males [49].…”
Section: Discussionsupporting
confidence: 92%
“…Al Dallal [37] and others reported older age and less glycemic control in anemic patients in comparison with non-anemic patients [47] [56]. In our study, there was a trend towards higher HbA1c in anemic participants but it did not reach a statistical significance (p = 0.072).…”
Section: Discussioncontrasting
confidence: 80%
“…A growing body of evidence linking dysregulated iron metabolism and T2D has been described over the years [ 5 , 6 , 7 ]. Whereby, both conditions of iron deficiency anaemia [ 8 , 9 ] and in some instances iron overload [ 6 , 10 , 11 ] have been widely reported in patients with T2D. The reported different relationships between poor glucose control and iron metabolism sparked interest in investigating iron metabolism in T2D, particularity on the modulators of iron intake, release, and transportation.…”
Section: Introductionmentioning
confidence: 99%
“…34 Growing evidence indicates that anemia in T2DM patients is a strong and independent indicator of increased risk for diabetes-related macrovascular and microvascular complications. 10,[35][36][37][38] It causes early occurrence and rapid progression of complications like diabetic nephropathy, diabetic retinopathy, diabetic neuropathy, end-stage renal diseases, ischemic heart disease, and nonhealing diabetic foot ulcers. 35 As in Ethiopia with an increasing incidence of DM, 39 it becomes mandatory to be aware of such co-morbidities at the earliest.…”
Section: Introductionmentioning
confidence: 99%